in a Middle-Aged Male With Liver Disease - Kevin Trong Dao MD; Carlos D'Assumpcao MD; Rupam Sharma MD; Arash Heidari MD (SAGE Publishing, 2024)
Clostridium paraputrificum is a gram-positive anaerobic spore-forming bacillus with a pathological prevalence of <1% among all Clostridium species. However, despite being a rare bacterium, there have been reported cases of C paraputrificum causing a wide range of varying pathologies. Herein presented is a case of cirrhosis secondary to alcoholism complicated by developing C paraputrificum bacteremia suspected due to gastrointestinal mucosal damage. There is literature demonstrating certain comorbid conditions having an impact on the overall prognosis of patients with C paraputrificum bacteremia.